The association of urinary sodium excretion and the need for renal replacement therapy in advanced chronic kidney disease: a cohort study - Mazarova, Andrea; Molnar, Amber O; Akbari, Ayub; Sood, Manish M; Hiremath, Swapnil; Burns, Kevin D; Ramsay, Timothy O; Mallick, Ranjeeta; Knoll, Gregory A; Ruzicka, Marcel (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background Restriction of dietary sodium is routinely recommended for patients with chronic kidney disease (CKD). Whether or not sodium intake is associated with the progression of CKD and mortality remains controversial. We evaluated the association of urinary sodium excretion (as a surrogate for sodium intake) on the need for renal replacement therapy and mortality in patients with advanced CKD. Methods We conducted a retrospective study of patients followed at a CKD clinic of a tertiary care hospital from January 2010 to December 2012. Adult patients with advanced CKD (estimated glomerular filtration rate (eGFR) <30 ml/min/1.73 m2) were included. Using a time-to-event analysis, we examined the association of urinary sodium excretion as a continuous and also as a categorical variable (categorized as low sodium diet - LSD (<100 mEq/day), medium sodium diet - MSD (100–150 mEq/day), and high sodium diet - HSD (>150 mEq/day) and the outcomes of interest. The primary outcome was defined as composite of progression to end-stage renal disease requiring any type of renal replacement therapy and mortality. The secondary outcome was change in eGFR/year. Results 341 patients (82 LSD, 116 MSD and 143 HSD) were included in the study (mean follow up of 1.5 years) with a mean eGFR decline of 2.7 ml/min/1.73 m2/year. 105 patients (31 %) required renal replacement therapy and 10 (3 %) died. There was no association between urinary sodium excretion and change in the eGFR or need for renal replacement therapy and mortality in crude or adjusted models (unadjusted HR 1.002; 95%CI 1.000–1.004, adjusted HR 1.001; 95%CI 0.998–1.004). Conclusion In patients with advanced CKD (eGFR < 30 ml/min/1.73 m2), sodium intake does not appear to impact the progression of CKD to end-stage renal disease; however, more definitive studies are needed.